1997
DOI: 10.1590/s0104-11691997000400002
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos ético-legais da retirada e transplante de tecidos, órgãos e partes do corpo humano

Abstract: As autoras fazem uma análise crítica da legislação em vigor relativa aos transplantes de órgãos, tecidos e partes do corpo humano, e tecem comentários sobre os artigos pertinentes a eles nos respectivos códigos de ética médica e da enfermagem, alertando os profissionais de enfermagem para a necessidade de registrarem as infrações cometidas contra o cliente, à luz desses códigos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
15

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 0 publications
1
1
0
15
Order By: Relevance
“…Although the pain of loss continues, the attitude of donation comforts and brings satisfaction (18) . This corroborates the idea that there are two values to be preserved, the life and dignity of the deceased donor, because this continues to represent the quality of the person to which it belonged (19) . In addition, there is a tendency of relatives consenting to a donation, when they are well informed about the concept of brain death and the humanistic purpose of donating (20)(21)(22) .…”
Section: Tissue and Organ Donation And The Relationship With The Bodysupporting
confidence: 81%
“…Although the pain of loss continues, the attitude of donation comforts and brings satisfaction (18) . This corroborates the idea that there are two values to be preserved, the life and dignity of the deceased donor, because this continues to represent the quality of the person to which it belonged (19) . In addition, there is a tendency of relatives consenting to a donation, when they are well informed about the concept of brain death and the humanistic purpose of donating (20)(21)(22) .…”
Section: Tissue and Organ Donation And The Relationship With The Bodysupporting
confidence: 81%
“…Um dilema ético é uma situação onde o indivíduo pode ver dois lados de um problema, sem que exista opção moral claramente certa ou errada que justifique decisão óbvia (9) . Os artigos destacam os dilemas e conflitos éticos associados à assistência de Enfermagem, ao diagnós-tico de Enfermagem, ao código de ética e a formação ética do enfermeiro (10)(11)(12)(13)(14) . Alguns artigos assinalam que a assistência à saúde é passível de questões e dilemas éticos, que, se não resolvidos adequadamente, podem comprometer a atuação profissional, a qualidade do atendimento e a autonomia do paciente (15)(16) .…”
Section: Discussionunclassified
“…Alguns artigos assinalam que a assistência à saúde é passível de questões e dilemas éticos, que, se não resolvidos adequadamente, podem comprometer a atuação profissional, a qualidade do atendimento e a autonomia do paciente (15)(16) . Estudos apontam que muitos enfermeiros vêm experimentando novas exigências éticas impostas por uma sociedade multicultural que, quando confrontados com dilemas éticos tendem a usar as convenções como orientação predominante dos seus critérios de decisão e não as necessidades dos pacientes e seu bemestar (11)(12) . Esta prática de seguir as convenções em vez de perseguir o melhor para o paciente constitui um obstáculo importante para o enfermeiro assumir uma postura ética adequada nas suas ações.…”
Section: Discussionunclassified
“…Two papers were found that orient nurses to problematize some of the current health discourse. One of them (10) evidences nurses' conduct of omission in patient information, this nursing works much more with aspects related to the benefits, to the detriment of the risks and consequences of the organ transplantation process. It also focuses on the high social cost and technology used in transplantations, bringing to mind the need for studies that assess the problems met.…”
Section: Responsibility Towards New Discoursesmentioning
confidence: 99%